2022
DOI: 10.1002/ecy.3877
|View full text |Cite
|
Sign up to set email alerts
|

Embolism resistance explains mortality and recovery of five subtropical evergreen broadleaf trees to persistent drought

Abstract: Subtropical evergreen broadleaf forests (SEBF) are experiencing and expected to suffer more frequent and severe drought events. However, how the hydraulic traits directly link to the mortality and recovery of SEBF trees remains unclear. In this study, we conducted a drought-rewatering experiment on tree seedlings of five dominant species to investigate how the hydraulic traits were related to tree mortality and the resistance and recovery of photosynthesis (A) and transpiration (E) under different drought seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
(108 reference statements)
1
2
0
Order By: Relevance
“…The magnitude of P 50 , which represents the embolism resistance of plants [1,49], and HSM, which can predict species mortality [1,7,50], are important parameters in assessing plant responses to drought. It has been established in previous studies that species with lower P 50 values and higher HSM 50 values exhibit higher resistance to exogenous stresses and have longer survival rates [51,52]. Here, P 50 values for both R. soongorica and S. passerina were significantly higher under the chronic and flash drought treatments compared to the control (Figure 2D), indicating that drought reduces the plants' ability to resist embolization.…”
Section: Response Of Plant Traits To Droughtsupporting
confidence: 50%
“…The magnitude of P 50 , which represents the embolism resistance of plants [1,49], and HSM, which can predict species mortality [1,7,50], are important parameters in assessing plant responses to drought. It has been established in previous studies that species with lower P 50 values and higher HSM 50 values exhibit higher resistance to exogenous stresses and have longer survival rates [51,52]. Here, P 50 values for both R. soongorica and S. passerina were significantly higher under the chronic and flash drought treatments compared to the control (Figure 2D), indicating that drought reduces the plants' ability to resist embolization.…”
Section: Response Of Plant Traits To Droughtsupporting
confidence: 50%
“…The magnitude of P 50 can reflect the embolic resistance of plants [9,33]. Generally, species with low P 50 are more resistant to damage from exogenous stresses and plants survive longer [34,35]. We found that after drought treatment, compared with the control, although there was no significant change in embolism resistance in the 2 drought groups, the values increased with the intensity of drought stress, indicating that the stronger the drought stress, the weaker the embolism resistance of the stems.…”
Section: The Trade-off Between Hydraulic Effectiveness and Safetymentioning
confidence: 64%
“…embolism). Lower (more negative) values of P 50 have been associated with higher resistance to drought and less mortality [53][54][55]. We measured P 50 in dominant trees in valleys and hills for three sites in South America, spanning a rainfall gradient from 1370 to 2245 mm yr −1 associated with an increase in dry season length and intensity.…”
Section: Introductionmentioning
confidence: 99%